SYNTHESIS AND SPECTROSCOPIC STUDIES OF COPPER(II)/COBALT(III) CYANIDE COMPOUNDS WITH IMIDAZOLE, 1-METHYLIMIDAZOLE, AND 2-METHYLIMIDAZOLE - Kürkçüoğlu, Güneş Süheyla; Karaağaç, Dursun; Kekeç, Seray (Eskisehir Technical University, 2025)
New Cu(II)/Co(III) cyanide compounds, [Cu3(L)4Co2(CN)12]?nH2O, with imidazole and methyl derivatives of imidazole have been synthesized in powder form and analyzed using elemental analyses, vibrational (FT-IR and Raman) spectroscopy, and powder X-ray diffraction (PXRD). The elemental analyses of all compounds for C, H, and N were performed and formulas of the compounds were calculated according to the results obtained. In addition, the phase purity of the compounds was confirmed through powder X-ray diffraction (PXRD) analysis. The results of PXRD patterns and vibrational spectroscopic show that the structural characteristics of Cu-Co-L [L = Imidazole(im), 1-methylimidazole(1-meim), and 2-methylimidazole(2-meim)] compounds are analogous to each other. The spectral properties of the Cu-Co-L compounds were obtained by considering the characteristic peak values of cyanide, imidazole, 1-methylimidazole, and 2-methylimidazole ligands
SYNTHESIS AND SPECTROSCOPIC STUDIES OF COPPER(II)/COBALT(III) CYANIDE COMPOUNDS WITH IMIDAZOLE, 1-METHYLIMIDAZOLE, AND 2-METHYLIMIDAZOLE
Keywords: Inorganic Green Chemistry; İnorganik Yeşil Kimya